Estratégias de reparo em Onset Simples utilizadas por crianças com desenvolvimento fonológico normal e desviante - Ghisleni, Maria Rita Leal (2009)
Repair strategies represent the resources used to adequate the accomplishment of the target-system to the child‟s phonological system. Children use these resources instead of the segment and/or syllabic structure that they do not know or instead of the productions they do not master yet. This study was made with the objective of describing and comparing the repair strategies used in the Simple Onset position by subjects with normal phonological development (NPD) and subjects with evolutional phonological disorder (EPD), besides verifying the repair strategies used by the subjects with different severity levels of EPD. In this research, we used speech samples containing the production of Simple Onset of 36 subjects (18 boys and 18 girls), aged between 1:2 and 4:2; 29, with NPD, and 12 subjects (6 boys and 6 girls), aged between 4:00 and 6:11;29, with EPD. The data were statically analyzed in the Computer Package VARBRUL in Windows environment (Varbwin). The repair strategies used by the subjects with NPD were: phoneme omission (32%), syllable omission (19%), desonorization (13%), semivocalization (13%), anteriorization (9%), posteriorization (5%), liquid substitution /r/[l] (5%), others (3%) and plosivization (1%). In the EPD subjects, it was observed: anteriorization (31%), phoneme omission (19%), posteriorization (13%), desonorization (11%), others (8%), plosivization (8%), semivocalization (7%), liquid substitution /r/[l] (2%) and syllable omission (1%). It is possible to see more similarities than differences in the favorable variables in the achievement of the strategies in the NPD and EPD. As for the repair strategies used, considering the severity of the EPD, the informants with severe disorder (SD) have a higher probability of producing plosivization, posteriorization, semivocalization and others. The Moderate-Severe Disorder (MSD) favors anteriorization, desonorization, among others. The Mild-Moderate Disorder (AMD), on the other hand, favors posteriorization, semivocalization and desonorization. As for the Mild Disorder (MD), there were more occurrences of posteriorizations and anteriorizations. The higher the level of severity of the phonological disorder, the more children use repair strategies, whether because they do not know the segment yet or because they do not master its production.